Diffracted X-ray Blinking Tracks Single Protein Motions. Issue 1 (December 2018) - Sekiguchi, Hiroshi; Kuramochi, Masahiro; Ikezaki, Keigo; Okamura, Yu; Yoshimura, Kazuki; Matsubara, Ken; Chang, Jae-Won; Ohta, Noboru; Kubo, Tai; Mio, Kazuhiro; Suzuki, Yoshio; Chavas, Leonard; et al.
Abstract Single molecule dynamics studies have begun to use quantum probes. Single particle analysis using cryo-transmission electron microscopy has dramatically improved the resolution when studying protein structures and is shifting towards molecular motion observations. X-ray free-electron lasers are also being explored as routes for determining single molecule structures of biological entities. Here, we propose a new X-ray single molecule technology that allows observation of molecular internal motion over long time scales, ranging from milliseconds up to 103 seconds. Our method uses both low-dose monochromatic X-rays and nanocrystal labelling technology. During monochromatic X-ray diffraction experiments, the intensity of X-ray diffraction from moving single nanocrystals appears to blink because of Brownian motion in aqueous solutions. X-ray diffraction spots from moving nanocrystals were observed to cycle in and out of the Bragg condition. Consequently, the internal motions of a protein molecule labelled with nanocrystals could be extracted from the time trajectory using this diffracted X-ray blinking (DXB) approach. Finally, we succeeded in distinguishing the degree of fluctuation motions of an individual acetylcholine-binding protein (AChBP) interacting with acetylcholine (ACh) using a laboratory X-ray source.